2003
DOI: 10.1007/s00442-002-1151-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of experimental food supplementation on movements of juvenile northern goshawks (Accipiter gentilis atricapillus)

Abstract: In the Materials and methods section, under Food supplementation experiment, 3rd paragraph, 3rd sentence: Table 1 in Ward and Kennedy 1996 should not have been linked in the online version.In Fig. 2: the number over the second bar from the left should be 10 and not 7.The online version of the original article can be found at http:// dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Food dumps in the western Scotland reintroduction were provided close to release sites to provide newly released birds with an easy food source (Love 1983) and as we © 2009 British Trust for Ornithology, Bird Study, 56, [177][178][179][180][181][182][183][184][185][186] found no difference in NDD according to stage of the reintroduction, the implication is thus that the provisioning did not apparently serve to 'tie' released birds close to the point of release long enough to affect subsequent dispersal (cf. Kennedy & Ward 2003). This may suggest that food dumps may influence the survival/condition of released birds but do not affect natal dispersal, if a subsidiary objective of dumps is to retain juveniles' presence close to the release site to keep them in a known 'safe' location.…”
Section: Discussionmentioning
confidence: 99%
“…Food dumps in the western Scotland reintroduction were provided close to release sites to provide newly released birds with an easy food source (Love 1983) and as we © 2009 British Trust for Ornithology, Bird Study, 56, [177][178][179][180][181][182][183][184][185][186] found no difference in NDD according to stage of the reintroduction, the implication is thus that the provisioning did not apparently serve to 'tie' released birds close to the point of release long enough to affect subsequent dispersal (cf. Kennedy & Ward 2003). This may suggest that food dumps may influence the survival/condition of released birds but do not affect natal dispersal, if a subsidiary objective of dumps is to retain juveniles' presence close to the release site to keep them in a known 'safe' location.…”
Section: Discussionmentioning
confidence: 99%
“…Kuussaari et al, 1996 ;Hanski et al, 2002;Schneider, Dover & Fry, 2003). Experimental food supplementation decreased the emigration propensity of juvenile northern goshawks Accipiter gentilis (Kennedy & Ward, 2003). As both the density of competitors and food levels together determine the per capita resources available for a population, effects of food availability are predicted to vary with population density.…”
Section: (B ) Food Availabilitymentioning
confidence: 99%
“…To accomplish this, we calculated 15 forest attribute area covariates for each of the seven periods within 12-ha, 73-ha, 243-ha, and 2023-ha circles centered on the nest site or point location (Table S1). These areas corresponded to the: 12-ha nest area suggested by Reynolds et al (1992) and Graham et al (2015); 73-ha nest area defined by the USDAFS Forest Plan direction for goshawk habitat management (USDAFS 2006(USDAFS , 2016; 243-ha recommended post-fledging area (PFA; Kennedy et al 1994), and 2023-ha foraging area (Kennedy 2003).…”
Section: Suitementioning
confidence: 99%
“…Conservation of American Goshawks ( Accipiter atricapillus [Chesser et al 2023]; hereafter goshawks) has been contentious in relation to forest management in North America (Squires and Kennedy 2006). Since the early 1990s, concern over negative effects of timber management practices on goshawk nesting, foraging, and post-fledging habitat use (Crocker-Bedford 1990) led to litigation concerning forest management guidelines and petitions to list several goshawk populations under the US Endangered Species Act (Kennedy 2003). Litigation focused on timber management practices in the southwestern USA that removed mature growth forest because high-quality nesting habitat for goshawks is generally considered to be contiguous tracts of older growth or mature forest, due to the relatively large home range sizes, territoriality, and prey needs of goshawks (Boal et al 2003, Reynolds et al 2006, Squires and Kennedy 2006).…”
Section: Introductionmentioning
confidence: 99%